P-174 Chronic Enteropathy Associated with SLCO2A1 Gene, Encoding Prostaglandin Transporter (CEAS). (March 2016) - Umeno, Junji; Hisamatsu, Tadakazu; Esaki, Motohiro; Hirano, Atsushi; Kochi, Shuji; Watanabe, Kenji; Aoyagi, Kunihiko; Hirai, Fumihito; Matsui, Toshiyuki; Yao, Tsuneyoshi; Hibi, Toshifumi; Kanai, Takanori; et al.
Abstract : Background: The widespread use of capsule endoscopy and balloon endoscopy has led to an increasing chance of encountering small intestinal pathology. Previously, we have proposed a rare clinicopathologic entity characterized by multiple small intestinal ulcers of nonspecific histology and chronic, persistent gastrointestinal bleeding as chronic nonspecific multiple ulcers of the small intestine (CNSU). Because conventional therapies for Crohn's disease (CD) including anti-tumor necrosis factor-alpha antibody therapy are ineffective for CNSU, recognition and precise diagnosis of CNSU are critical. Although CNSU predominantly occurs in females, it seems to be an autosomal recessive inherited disorder because of frequent parental consanguinity. Methods: To identify the genetic abnormality of this disorder, we performed whole-exome sequencing and segregation analysis in family members of CNSU patients, and sequencing analysis in other CNSU patients. Subsequently, we genotyped the identified mutation sites in patients previously diagnosed as CD to identify concealed CNSU patients. Results: By whole-exome sequencing in 5 Japanese patients with CNSU and one unaffected individual, we found 4 candidate mutations in the SLCO2A1 gene, encoding a prostaglandin transporter. The pathogenicity of the mutations is supported by in silico prediction, segregation analysis and genotyping data in controls. By Sanger sequencing of the coding regions of this gene, 11 of 12 CNSU patients were found to have homozygous or compound heterozygous SLCO2A1 mutations. Among 603 CD patients, 2 were found to carry compound heterozygous SLCO2A1 mutations and corrected their diagnosis as CNSU. In total, we identified recessive SLCO2A1 mutations located at 7 sites in 18 of 19 CNSU patients. Conclusions: The mutations in the SLCO2A1 gene are assumed to be the causal genetic abnormalities of CNSU. We propose a more appropriate nomenclature, "chronic enteropathy associated with SLCO2A1 gene" (CEAS), for this disease. Genetic analysis can clearly differentiate CEAS from other gastrointestinal disorders including CD and NSAID-induced enteropathy.